2002
DOI: 10.1038/sj.onc.1206044
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of caspase 3 in breast cancer: a possible mechanism for chemoresistance

Abstract: Caspase-3 is a member of the cysteine protease family, which plays a crucial role in apoptotic pathways by cleaving a variety of key cellular proteins. Caspase-3 can be activated by diverse death-inducing signals, including the chemotherapeutic agents. The purpose of this study was to determine the levels of caspase-3 expression in breast tumor samples and to determine whether alterations in its expression can affect their ability to undergo apoptosis. Primary breast tumor and normal breast parenchyma samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
274
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(294 citation statements)
references
References 38 publications
15
274
0
5
Order By: Relevance
“…Reconstitution of caspase 3 expression enhanced apoptosis induced by staurosporine and chemotherapeutic agents. 29,38 These data suggest that caspase 3 deficiency could at least partially account for resistance of MCF-7 cells to DR4. On the other hand, apoptosis induced by overexpression of the proapoptotic bcl-2 family member Bak was not impaired in MCF-7 cells as compared to the caspase 3-expressing HeLa cells.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Reconstitution of caspase 3 expression enhanced apoptosis induced by staurosporine and chemotherapeutic agents. 29,38 These data suggest that caspase 3 deficiency could at least partially account for resistance of MCF-7 cells to DR4. On the other hand, apoptosis induced by overexpression of the proapoptotic bcl-2 family member Bak was not impaired in MCF-7 cells as compared to the caspase 3-expressing HeLa cells.…”
Section: Discussionmentioning
confidence: 83%
“…However, this deficiency might not be restricted to MCF-7 cell line, as recent evaluation of caspase 3 mRNA and protein in primary breast tumors demonstrated lack of expression in 75% of the samples. 29 To determine whether the absence of caspase 3 expression in MCF-7 cells was unique, we evaluated expression of caspases in our panel of breast cancer cell lines by Western blotting. No caspase 3 protein was detected in MCF-7 cells, while all other cell lines expressed readily detectable level of protein (Fig 5b).…”
Section: Expression Of Genes Involved In Trail-induced Apoptosis In Bmentioning
confidence: 99%
“…156 CASP3 polymorphisms in some lung cancer patients also show significantly decreased risk of disease. 157 Although it was reported that caspase-3 expression is significantly reduced in breast cancer cells, cancer tissue and even in the normal parenchyma surrounding tumors, 158 several groups have demonstrated the converse. Higher levels of caspase-3 protein were found in malignant, compared to nonmalignant breast tissue, and coincided with increased apoptosis.…”
Section: Caspases In Tumorigenesismentioning
confidence: 99%
“…Caspase-3 is a fundamental protein frequently used to investigate apoptotic pathways (Devarajan et al, 2002). During apoptosis, cytochrome-c (cyt-c) releases from mitochondria into the cytosol and induces the caspase activation pathway starting with procaspase-9 activation.…”
Section: Introductionmentioning
confidence: 99%